Membangun Kemandirian Pariwisata: Pemberdayaan Pemuda Nemberala Melalui Pengembangan Berkelanjutan Dan Kewirausahaan Untuk Optimalisasi Potensi Wisata - Rolland E Fanggidae; Yuri S Faah; Wehelmina M Ndoen; Ni Putu Nursiani; Efandri Agustian (Universitas Muhammadiyah Mataram, 2026)
Abstract: Nemberala Beach in West Rote Regency, East Nusa Tenggara, boasts extraordinary tourism potential with its exotic natural beauty. However, tourism management in this area remains suboptimal. Four main challenges hamper tourism development: limited technical competency among young people, lack of affordable accommodation infrastructure, reliance on imported food, and low entrepreneurial capacity. The main objectives of the Community Service Program (PKM) are (1) improving the technical skills of young people in areas relevant to Nemberala's tourism needs, (2) creating micro-enterprises based on local potential independently managed by young people, and (3) reducing dependence on external investors through the sustainable use of local resources. This Community Service Program (PKM) is designed with a participatory and holistic approach to address partner challenges at Nemberala Beach, particularly in the areas of organic agricultural production, tourism business management, and digital marketing. The implementation method is divided into four main stages: preparation, implementation, evaluation, and sustainability, involving active partner participation and multi-stakeholder collaboration. The outcomes of this PKM activity are: (1) improving the technical skills of young people in areas relevant to Nemberala's tourism needs; (2) Creating micro-enterprises based on local potential that are independently managed by youth; (3) Reducing dependence on external investors through the sustainable use of local resources.Abstrak: Pantai Nemberala di Kabupaten Rote Barat, Nusa Tenggara Timur, memiliki potensi wisata yang luar biasa dengan keindahan alam yang eksotis. Namun, pengelolaan pariwisata di daerah ini masih belum optimal. Terdapat empat tantangan utama yang menghambat pengembangan pariwisata, yaitu keterbatasan kompetensi teknis kaum muda, kurangnya infrastruktur penginapan murah, ketergantungan pada makanan impor, dan rendahnya kapasitas kewirausahaan. Tujuan utama PKM adalah (1) meningkatkan keterampilan teknis pemuda dalam bidang yang relevan dengan kebutuhan pariwisata Nemberala, (2) menciptakan usaha mikro berbasis potensi lokal yang dikelola mandiri oleh pemuda, serta (3) mengurangi ketergantungan pada investor eksternal melalui pemanfaatan sumber daya lokal secara berkelanjutan. Program Pengabdian Kepada Masyarakat (PKM) ini dirancang dengan pendekatan partisipatif dan holistik untuk menjawab permasalahan mitra di Pantai Nemberala, khususnya dalam bidang produksi pertanian organik, manajemen usaha pariwisata, dan pemasaran digital. Metode pelaksanaan dibagi ke dalam empat tahap utama: persiapan, implementasi, evaluasi, dan keberlanjutan, dengan melibatkan partisipasi aktif mitra serta kolaborasi multi-pihak. Hasil dari kegiatan PKM ini adalah: (1) Meningkatkan keterampilan teknis pemuda dalam bidang yang relevan dengan kebutuhan pariwisata Nemberala; (2) Menciptakan usaha mikro berbasis potensi lokal yang dikelola mandiri oleh pemuda; (3) Mengurangi ketergantungan pada investor eksternal melalui pemanfaatan sumber daya lokal secara berkelanjutan.